2023
DOI: 10.1097/ccm.0000000000005988
|View full text |Cite
|
Sign up to set email alerts
|

Asynchrony Injures Lung and Diaphragm in Acute Respiratory Distress Syndrome*

Abstract: Objectives: Patient-ventilator asynchrony is often observed during mechanical ventilation and is associated with higher mortality. We hypothesized that patient-ventilator asynchrony causes lung and diaphragm injury and dysfunction. Design: Prospective randomized animal study. Setting: University research laboratory. Subjects: Eighteen New Zealand White rabbits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In turn, patient-ventilator asynchronies could have an adverse effect on the diaphragm. In a recent study in a rabbit ARDS model, reverse triggering and breath stacking resulted in both diaphragm and lung injury [8 ▪ ]. However, no indications of diaphragm myotrauma caused by patient-ventilator asynchronies were found in another study in pigs with ARDS [44].…”
Section: Auto-positive End-expiratory Pressurementioning
confidence: 93%
See 1 more Smart Citation
“…In turn, patient-ventilator asynchronies could have an adverse effect on the diaphragm. In a recent study in a rabbit ARDS model, reverse triggering and breath stacking resulted in both diaphragm and lung injury [8 ▪ ]. However, no indications of diaphragm myotrauma caused by patient-ventilator asynchronies were found in another study in pigs with ARDS [44].…”
Section: Auto-positive End-expiratory Pressurementioning
confidence: 93%
“…Finally, certain types of patient-ventilator asynchrony may contribute to diaphragm myotrauma due to the occurrence of injurious eccentric (lengthening) contractions [7]. In an animal model of acute respiratory distress syndrome (ARDS), reverse triggering caused eccentric contractions of the diaphragm with concomitant diaphragm myotrauma [8 ▪ ]. This has been discussed in more detail in a recent narrative review [9].…”
Section: Mechanisms Of Critical Illness Associated Diaphragm Dysfunctionmentioning
confidence: 99%
“…The hypothesis of eccentric myotrauma as a mechanism of ventilator-induced diaphragm dysfunction is intriguing, but its clinical relevance remains uncertain. Pre-clinical studies have demonstrated that dyssynchronous diaphragm contractions are associated with acute diaphragm injury and dysfunction [ 5 7 ] and that eccentric loading results in acute diaphragmatic weakness [ 8 ]. Diaphragm biopsies in humans including mechanically ventilated patients manifest evidence of acute load-induced injury and inflammation [ 9 , 10 ], suggesting that load-induced injury occurs in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of Critical Care Medicine , Hashimoto et al (11) conducted an experimental study to test the hypothesis that some forms of dyssynchrony may cause lung and diaphragm injury. In a rabbit model of acute lung injury, the authors used phrenic nerve stimulation to induce breath stacking or reverse triggering for a period of 4 hours.…”
mentioning
confidence: 99%
“…The clinical benefit of the lung-protective and diaphragm-protective approach, and of ameliorating these forms of dyssynchrony, remains to be tested in clinical trials. The work by Hashimoto et al (11) highlights the urgent need for these trials.…”
mentioning
confidence: 99%